miRNA-based regulation in growth plate cartilage: mechanisms, targets, and therapeutic potential - Thakore, Prachi; Delany, Anne M. (Frontiers in Endocrinology, 2025)
MicroRNAs (miRNAs) are critical regulators of the skeleton. In the growth plate, these small non-coding RNAs modulate gene networks that drive key stages of chondrogenesis, including proliferation, differentiation, extracellular matrix synthesis and hypertrophy. These processes are orchestrated through the interaction of pivotal pathways including parathyroid hormone-related protein (PTHrP), Indian hedgehog (IHH), and bone morphogenetic protein (BMP) signaling. This review highlights the miRNA-mRNA target networks essential for chondrocyte differentiation. Many miRNAs are differentially expressed in resting, proliferating and hypertrophic cartilage zones. Moreover, differential enrichment of specific miRNAs in matrix vesicles is also observed, providing means for chondrocytes to influence the function and differentiation of their neighbors by via matrix vesicle protein and RNA cargo. Notably, miR-1 and miR-140 emerge as critical modulators of chondrocyte proliferation and hypertrophy by regulating multiple signaling pathways, many of them downstream from their mutual target Hdac4. Demonstration that a human gain-of-function mutation in miR-140 causes skeletal dysplasia underscores the clinical relevance of understanding miRNA-mediated regulation. Further, miRNAs such as miR-26b have emerged as markers for skeletal disorders such as idiopathic short stature, showcasing the translational relevance of miRNAs in skeletal health. This review also highlights some miRNA-based therapeutic strategies, including innovative delivery systems that could target chondrocytes via cartilage affinity peptides, and potential applications related to treatment of physeal bony bridge formation in growing children. By synthesizing current research, this review offers a nuanced understanding of miRNA functions in growth plate biology and their broader implications for skeletal health. It underscores the translational potential of miRNA-based therapies in addressing skeletal disorders and aims to inspire further investigations in this rapidly evolving field.